Tiller hierarchy and defoliation frequency determine bud viability in the grass Poa ligularis - Busso, Carlos Alberto; Gittins Lopez, Cecilia Gabriela; Becker, Guillermo Fernando; Ghermandi, Luciana (Wiley, 2024)
Bud viability after various defoliation frequency treatments was determined in the perennial bunchgrass Poa ligularis under arid field conditions from 2002 to 2005. Bud respiratory activity was examined on various stem base hierarchies using the tetrazolium test, as validated with the vital stain Evan’s blue. The hypothesis of this work was that the total and viable axillary bud numbers on stem bases of all study stem base hierarchies are reduced as defoliation frequency increases. Interpretation of the results differed when they were expressed as a percentage rather than on a number per stem base basis. The total number of axillary buds per stem base was similar in all defoliation frequencies. When the results were expressed on a percentage basis, the order on stem bases having metabolically active buds was daughter tillers > stem bases with green tillers > stem bases without green tillers in all defoliation frequencies. The reverse order was found when considering dead buds. How the results are expressed thus deserves our attention when reporting results on bud viability in perennial grasses. An increased defoliation frequency increased the percentage of dead and dormant buds after the third or fourth defoliation of P. ligularis during the 1st study year. These percentages of bud viability, however, increased after the first defoliation during the 2nd study year. Bud viability was affected not only by the cumulative effects of defoliation but also by climatic variables throughout the seasons. However, our results show that P. ligularis can be defoliated up to twice a year without affecting bud viability, and thus its potential capacity for regrowth after defoliation.